(untitled) (Journal of Partial Differential Equations, 2020)
The target of this paper is the long time behaviour of solutions for a generalized Ginzburg-Landau equation on IR. The authors establish the existence of a global attractor of finite Hausdorff and fractal dimension in a weighted Hilbert space for the equation.